Are Child Abusers Sexually Attracted to Submissiveness? Assessment of Sex-Related Cognition With the Implicit Association Test. (August 2016) - Kanters, Thijs; Hornsveld, Ruud H. J.; Nunes, Kevin L.; Huijding, Jorg; Zwets, Almar J.; Snowden, Robert J.; Muris, Peter; van Marle, Hjalmar J. C.
Child sexual abuse is associated with social anxiety, low self-esteem, and intimacy deficits. This, in combination with the core belief of a dangerous world, might suggest that child abusers are sexually attracted to submissiveness. The Implicit Association Test (IAT) was used to examine this hypothesis. Results indicated that child abusers have a stronger sexual preference for submissiveness than rapists, although there were no differences between child abusers and non-sexual offenders. Multinomial logistic regression analysis revealed that submissive–sexy associations have incremental value over child–sex associations in differentiating child abusers from other offenders. The predictive value of both implicit associations was explored by correlating IAT scores with measures for recidivism risk, aggression, and interpersonal anxiety. Child abusers with stronger child–sex associations reported higher levels of interpersonal anxiety and hostility. More research on implicit cognition in sex offenders is required for a better understanding of what these and similar implicit measures are exactly measuring and what role implicit cognition may play in sexual offending.